النزوف الرحمية حول سن الضهي خبرة مشفى الأسد الجامعي باللاذقية - سلوم, نهاد (Latakia University Journal -Medical Sciences Series, 2019)
يعتبر سرطان باطن الرحم سرطان النساء المتقدمات في السن, ويتم تشخيصه في 90% من الحالات بعمر 50 سنة فما فوق, وهو أكثر سرطانات الجهاز التناسلي الأنثوي شيوعاً ويتميز في مراحله المبكرة بإنذار جيد لكن هذا الانذار يسوء عند وجود انتقالات إلى العضلة الرحمية أو اللمف أو عند وجود سوء تميز نسيجي لذلك فإن قياس سماكة البطانة الرحمية قبل حدوث الأعراض السريرية مفيد جد في التشخيص المبكر وتحسين الانذار علماً انها تقانة بسيطة متوافرة غير مكلفة وغير جارحة. تمت الدراسة في الفترة من 21/4/2003إلى21/11/2003 في قسم النسائية في مشفى الأسد الجامعي باللاذقية – كلية الطب – جامعة تشرين بلغت نسبة المراجعات بقصة نزف تناسلي لقسم النسائية 42.36% . وجد فرط تصنع بطانة الرحم بنسبة 19.15% عند المريضات في مرحلة ما حول سن الاياس منها 9.75% فرط تصنع مختلط ولم تشاهد حالات خبيثة . وجد سرطان باطن الرحم بنسبة 18.18% في مرحلة ما بعد الاياس. درست سماكة بطانة الرحم عند 64 مريضة قسمن لمجموعتين : أ‌- المجموعة الأولى (سماكة البطانة أقل من 5 ملم) 10 مريضات حيث بلغ متوسط سماكة البطانة 2.6 ملم. ب‌- المجموعة الثانية سماكة البطانة £ 5 ملم 54 مريضة بلغ متوسط سماكة البطانة 12.21 ملم شوهد عند مريضات المجموعة الأولى فرط تصنع بطانة رحم بسيط بنسبة 20% ولم تشاهد حالات فرط تصنع مختلط أو حالات خباثة . شوهد عند مريضات المجموعة الثانية فرط تصنع بطانة رحم عند 31.48% 11.1 % فرط تصنع مختلط كما شوهدت الخباثة في بطانة الرحم عند 3.7% . Uterine bleeding is an important symptom a lot of patient came to the gynecological clinc and department. It is repaited in women in all period of the life endometrial cancer is the older woman’s disease, and approximately 90% of cases are diagnosed in women 50 years of age or older. Endometrial cancer is most often highly differentiated and in the early stages has a normally good prognosis, But with myometrial or lymphatic spreading and low differentiation, the prognosis is worse( 90% versus 60%) . Therefore it is of importance to diagnose endometrial cancer as early as possible, preferaply before its cardinal symptom, postmenopausal bleeding in women occurs. Measurement of endometrial thickness by transvaginal sanograghy has been proposed as a possible noninvasive technique of making on early diagnosis. The efficacy of endometrial thickness measured by transvaginal sonograghy has been compard with histology obtained by curettage in the diagnosis of endometrial cancer in pre and postmenopausal women. The study has been performed at the Gynecological department in Al.Assad hospital lattakia from 21/4/2003-21/11/2003. The incidence of uterine bleeding was 42.36% The endometrial hyperplasia was 19.15% in premenopouse women, from it 9.75% is complicated hyperplasia, and no cancer seen. The endometrial cancer was 18.18% in post menpouse age. 64 women were peri or, post menopause was invited to attend for transvaginal sonograghy examination: A- Endometrial thickness <5 m.m: Simple hyperplasia 20%. no cancer or mixed hyperplasia is seen B- Endometrial thickness ³5 m.m:mixed hyperplasia was 11.1%, and endometrial cancer 3.7%